Smart Home System for Controlling Household Appliances Utilizing Photovoltaic Technology - Mohammad Khoiruddin; Endang Retnoningsih; Syahbaniar Rofiah (LPPM Universitas Islam 45 Bekasi, 2024)
Photovoltaic is a technology that functions to convert solar energy into electrical energy directly. The smart home system for controlling household appliances with Photovoltaic technology is a concept that integrates renewable technology and artificial intelligence to increase the efficiency and sustainability of energy use in households. By using the ESP32 microcontroller as the main control system to monitor and regulate power usage based on the availability of solar energy. The system starts by checking the solar voltage, if it is providing enough power to household appliances. If the solar voltage is insufficient the system will turn off non-essential equipment or reduce power consumption. Users can control the system via smartphone to activate household appliances as needed. The system uses an inverter to convert the DC voltage from the solar panels into the AC voltage required by household appliances. This research combines Photovoltaic and IoT technology in a Smart Home that can increase energy efficiency and support environmental conservation efforts. Research can make a positive contribution to the development of sustainable energy solutions for modern households.